THE OPPORTUNITIES AND CHALLENGES OF THE BIG DATA IMPLEMENTATION IN SOCIAL SCIENCE RESEARCH: A LITERATURE REVIEW - PELUANG DAN TANTANGAN BIG DATA DALAM PENELITIAN ILMU SOSIAL: SEBUAH KAJIAN LITERATUR - Vience Mutiara Rumata (BPSDMP Kominfo Manado, 2016)
In the era of digital information, data can be accessed, recorded, trajected, and analysed conveniencely. Big Data is not solely a trend amongst the exculsive group, instead, it marks the paradigm swift particularly to undersand the social processes. Data, which generated on social media, is an avalanche of Big Data era. For the academics, Big Data challenges the social researchers by the changing of unit of analysis from human to algortihms. This article discusses the opportunities and pitfalls of Big Data in social science research. This is a literature review that derived mainly from journals published in prominent scientific publications such as Taylor & Francis, Elsevier, and Sage. The main purpose is to yield a basic knowledge and fill the gap for non-computer scientists, regarding the implementation of Big Data in the research. The result that Big Data has opportunities to deliver the multidiscipline field of study (computer, social and statistic); overcome the limitation of convesional methods of data gathering (both quantitative and qualitative); and offers an analytical framework for sociology field of study. Big Data imposes challenges such as common understanding of Big Data, methodology and theory issues, and research ethic debates. Key words: Big Data, Social, Research, Opportunities, Challenges Memasuki era digital, segala data (informasi) mudah diakses, disimpan, ditelusuri, bahkan dianalisa. Big Data bukan sekadar tren yang dipopulerkan oleh kalangan eksklusif, melainkan sebuah penanda perubahan paradigma untuk memahami proses-proses sosial. Data yang dihasilkan di media sosial merupakan sebagian kecil dari “longsoran bola salju” di era Big Data. Bagi kalangan akademisi, Big Data telah memberikan tantangan bagi peneliti sosial dengan adanya perubahan unit analisis dari manusia menjadi algoritma. Artikel ini membahas peluang dan tantangan Big Data bagi peneliti sosial dari sisi literatur yang berasal dari publikasi luar negeri seperti Taylor & Francis, Elsevier, Sage publication. Tujuannya adalah untuk memberikan pemahaman mendasar sekaligus mengisi kesenjangan pengetahuan terkait implementasi Big Data dalam penelitian bagi ilmuwan non ilmu komputer. Hasil kajian ini menemukan bahwa ada tiga peluang Big Data: munculnya terobosan multidisiplin ilmu “computational social science”; menjawab keterbasan metode pengumpulan data konvensional baik kuantitatif maupun kualitatif; serta menawarkan kerangka analisis bagi ilmuwan sosiologi. Disamping peluang, ada tiga tantangan Big Data: pemahaman mendasar terkait data, isu metodologi dan teori serta isu etika penelitian. Kata kunci: Big Data, Sosial, Penelitian, Peluang, Tantangan